3D Printing and Product Assortment Strategy - Dong, Lingxiu; Shi, Duo; Zhang, Fuqiang (Management Science, 2022)
3D printing, as a production technology, differs from conventional technologies in three characteristics: design freedom—that is, it can handle certain product designs that conventional technologies cannot; quality distinction—that is, depending on the focal quality dimension, it can lead to a quality level superior or inferior to that of conventional technologies; and natural flexibility—that is, it is endowed with capacity flexibility without sacrificing operational efficiency. This paper investigates the joint impact of these characteristics when a firm selects conceptual designs to form its product assortment, taking into account the production-technology choices available for each design: 3D printing and two conventional technologies (dedicated and traditional flexible). Some designs can be processed by using any technology (generic), whereas others are specific to 3D printing (3D-specific). The firm selects designs to be handled by each technology and then invests accordingly in technology adoption, product development, capacity, and production. We characterize the structure of the optimal assortment based on the popularity of each design. Within the sets of generic designs and 3D-specific designs, respectively, the most popular designs should be included in the assortment; under a mild condition, the optimal assortment comprises the most popular ones among all the designs. Within the optimal assortment, 3D printing should handle the less popular generic designs than conventional technologies. We further demonstrate that the design freedom or improved quality associated with 3D printing may reduce the firm’s optimal product variety. In the absence of design freedom and quality distinction, natural flexibility by itself always enhances product variety; by contrast, traditional flexible technology may reduce product variety. Numerical study shows that 3D printing tends to be more valuable when popularities of the generic designs are distributed more evenly and when popularities of the 3D-specific designs are distributed less evenly. This paper was accepted by Vishal Gaur, operations management.